(untitled) - Bendell, Tony (London, 1998)
Benchmarking is a highly-effective structural approach to quality engineering and management that is finding wide acceptance among managers everywhere. It involves investigating industry's best practices, analyzing and evaluating one's own operation for opportunities, and implementing an action plan that includes the structure of goals, objective, and operating targets. This sure-fire guide shows managers, engineers, and quality personnel what the benchmarking process is all about, how it can help them, and how they can implement the process in their organization--to achieve spectacular results!
Keywords: Business management